Modeling of Seismic and Resistivity Responses during the Injection of CO2 in Sandstone Reservoir - Bin Omar, Muhamad Nizarul Idhafi (Universiti Teknologi PETRONAS, 2016)
Enhanced oil recovery plays vital role in production phase in a producing oil field. Initially, in many cases, like in Malay Basin, hydrocarbon will naturally flow to the well as respect to the reservoir pressure. But over time, hydrocarbon flow to the well will decrease as the pressure decrease and require recovery method so called enhanced oil recovery (EOR) to recover the hydrocarbon flow. Generally, EOR works by injecting substances, such as carbon dioxide (CO2) to form a pressure difference to establish a constant productive flow of hydrocarbon to production well. Monitoring CO2 performance is crucial in ensuring the right trajectory and pressure differences are established to make sure the technique works in recovering hydrocarbon flow. In this dissertation, we work on methods in monitoring CO2 performance by seismic and resistivity model, enabling geoscientists and reservoir engineers to monitor production behaviour as respect to CO2 injection.